A Retrospective Chart Review to Examine Failed Modified Brostrom Procedures for Chronic Lateral Ankle Instability. Issue 4 (22nd October 2020) - Rizzo, Kaitlyn; Brandle, Greggory; Cheney, Nicholas A.; Clark, Brian C.
Category: Ankle; Other Introduction/Purpose: Recurrent ankle injuries can lead to chronic ankle instability requiring surgical stabilization. Since the anterior talofibular ligament (ATFL) is the weakest of the lateral ankle ligaments, repair is often required in cases of chronic lateral ankle instability. Damage to the calcaneofibular ligament (CFL) is less common than the ATFL, but additional repair of it in these cases may be necessary to avoid this recurrent instability. A modified Brostrom procedure has been a widely accepted surgical approach to chronic lateral ankle instability if conservative measures fail. However, cases of recurrent instability even after initial stabilization surgery can present. The purpose was to examine reasoning for and rate of revision surgeries attempting to fix chronic lateral ankle instability as it relates to the ATFL and CFL integrity. Methods: A retrospective chart review was conducted to assess outcomes of a modified Brostrom procedure to determine underlying reasoning of the need for revision surgery by utilizing results of the anterior drawer and varus tilt tests. The files of these patients were examined via electronic health records to determine the reasoning for surgery. The preoperative and postoperative results of the anterior drawer test (ADT) and varus tilt test were used to examine ATFL and CFL integrity, respectively, in addition to operative notes. Results: 172 patients met criteria having undergone a modified Brostrom dual ligament repair procedure for lateral ankle instability by a single orthopedic foot and ankle surgeon. With a 3.49% revision rate in the patient population, the only similarity found in all of the patients was the presence of a positive varus tilt test indicating the CFL was a major contributor of failed correction via the modified Brostrom procedure. One patient had a positive ADT, and one had a mildly positive ADT. These ADT and varus tests were performed at various time points in the care of the patients. The average length between surgeries was calculated to be 624.2 days. This revision rate is higher than past studies but was limited to a few years under examination. Conclusion: In conclusion, the anterior drawer and varus tilt tests are utilized to determine the integrity of the ATFL and CFL in the lateral ankle ligament complex. In failed modified Brostrom procedures examined, the positive result was consistently in the varus tilt test, indicating that the CFL is the ligament most affected in these patients requiring additional surgery. However, these physical exam tests are only one way to examine the ankle and do not take additional pathologies of the lateral ankle into account. Additional studies are needed to examine long-term outcomes of the modified Brostrom procedure and reasoning for failure.